Evaluasi Pengelolaan Lansekap Pura Mengening, Desa Pakraman Saraseda, Kecamatan Tampaksiring, Kabupaten Gianyar, Provinsi Bali - UTAMI, KADEK AYU DIAH; SARWADANA, SANG MADE; SUDARSANA, ANAK AGUNG GEDE DALEM (Jurnal Arsitektur Lansekap, 2017)
Mengening temple is one of the cultural landscape that has malukat area but less affirmed malukat area with the washing area for residents and inadequate facilities are problems in the site. This research aims to determine the landscape management applied in Mengening temple. The method used in this research was survey method with observation, questionnaires, interviews, and literature study. The results of this study was a description of management applied by member of Saraseda village sescription of potentials and issues of landscaping management of Mengening temple in terms of management, space, structuring, and maintenance, along with descriptions of recommended efforts that can be done to improve the quality of management and recommendations for a workable floor plan. This recommendation given in the form of inputs that can be done to the government, managers, and the community so that it can be improve the quality of the Mengening temple management and maintain the sanctity and holiness of Mengening temple.